Valorization in Life and in Language - GRDZELYAN, ROUZAN (Bulletin of Yerevan University H: Russian Philology, 2021)
The article is devoted to one of the most important problems of modern semiotics and linguistics- the problem of the transformation of empirical fact in sign. Valorization is characteristic of all cultural spheres, particularly in the language and speech. The article attempts to dissect and describe the causes and processes that lead to the formation of the sign - in society, in the field of culture and language.
Keywords: valorization, valorization system, empirical system, speech stereotypes, mental stereotypes